Draft Genome Sequence of Clostridium estertheticum subsp. laramiense DSM 14864T, Isolated from Spoiled Uncooked Beef. - Palevich N; Palevich FP; Maclean PH; Jauregui R; Altermann E; Mills J; Brightwell G (American Society for Microbiology, 2019)
Clostridium estertheticum subsp. laramiense type strain DSM 14864 (ATCC 51254) was isolated from vacuum-packaged refrigerated spoiled beef. This report describes the generation and annotation of the 5.0-Mb draft genome sequence of C. estertheticum subsp. laramiense DSM 14864T.